The Nile Basin : national determinants of collective action - Waterbury, John (Yale University Press, 2002)
The supply and management of fresh water for the world's billions of inhabitants is likely to be one of the most daunting challenges of the 21st century. For countries that share river basins with others, questions of how best to use and protect precious water resources always become entangled in complex political, legal, environmental, and economic considerations. This text focuses on the issues that face all international river basins by examining in detail the Nile Basin and the ten countries that lay claim to its waters. John Waterbury applies collective action theory and international relations theory to the challenges of the ten Nile nations. Confronting issues ranging from food security and famine prevention to political stability, these countries have yet to arrive at a comprehensive understanding of how to manage the Nile's resources. Waterbury proposes a series of steps leading to the formulation of environmentally sound policies and regulations by individual states, the establishment of accords among groups of states, and the critical participation of third-party sources of funding like the World Bank. He concludes that if there is to be a solution to the dilemmas of the Nile Basin countries, it must be based upon contractual understandings, brokered by third-party funders, and based on the national interests of each basin state.